In vitro culture of in vivo-produced sheep, goat and cattle embryos - Barry, Daniel Malan (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD(Agric) (Animal Sciences))--University of Stellenbosch, 2005.